2022
DOI: 10.1212/wnl.0000000000201036
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Viruses in the Baltimore Longitudinal Study of Aging

Abstract: Background and Objectives.Although an infectious etiology of Alzheimer’s Disease (AD) has received renewed attention with a particular focus on herpes viruses, the longitudinal effects of symptomatic herpes viruses (sHHV) infection on brain structure and cognition remain poorly understood, as does the effect of sHHV on AD/neurodegeneration biomarkers.Methods.We used a longitudinal, community-based cohort to characterize the association of sHHV diagnoses with changes in 3T MRI brain volume and cognitive perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“… 41 In a study using data from the Baltimore Longitudinal Study of Aging, no associations were found between symptomatic herpesvirus infections and changes in brain volume or AD signature regions, although some associations were reported for other markers of dementia risk, including attentional decline and astrogliosis. 42 Null findings between HSV1 serostatus and whole brain atrophy were additionally reported in a cohort with parental history of early‐onset autosomal dominant AD. 43 In contrast, relationships between higher seroreactivity to HSV (either 1 or 2) and smaller hippocampal volume were reported in an analysis involving two small cohorts ( N = 349).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 41 In a study using data from the Baltimore Longitudinal Study of Aging, no associations were found between symptomatic herpesvirus infections and changes in brain volume or AD signature regions, although some associations were reported for other markers of dementia risk, including attentional decline and astrogliosis. 42 Null findings between HSV1 serostatus and whole brain atrophy were additionally reported in a cohort with parental history of early‐onset autosomal dominant AD. 43 In contrast, relationships between higher seroreactivity to HSV (either 1 or 2) and smaller hippocampal volume were reported in an analysis involving two small cohorts ( N = 349).…”
Section: Discussionmentioning
confidence: 91%
“…For example, serostatuses for C. pneumoniae , H. pylori , and CMV were not associated prospectively with dementia risk, whole brain volume, or white matter lesions in the Framingham cohort study 41 . In a study using data from the Baltimore Longitudinal Study of Aging, no associations were found between symptomatic herpesvirus infections and changes in brain volume or AD signature regions, although some associations were reported for other markers of dementia risk, including attentional decline and astrogliosis 42 . Null findings between HSV1 serostatus and whole brain atrophy were additionally reported in a cohort with parental history of early‐onset autosomal dominant AD 43 .…”
Section: Discussionmentioning
confidence: 95%
“…41 In a study using data from the Baltimore Longitudinal Study of Aging, no associations were found between symptomatic herpesvirus infections and changes in brain volume or AD signature regions, although some associations were reported for other markers of dementia risk, including attentional decline and astrogliosis. 42 Null findings between HSV1 serostatus and whole brain atrophy were additionally reported in a cohort with parental history of earlyonset autosomal dominant AD. 43 In contrast, relationships between higher seroreactivity to HSV (either 1 or 2) and smaller hippocampal volume were reported in an analysis involving two small cohorts (N = 349).…”
Section: Ta B L Ementioning
confidence: 90%